Calciphylaxis Episodes in the Australia and New Zealand Dialysis and Transplant Registry - Nigel D. Toussaint; Christopher E. Davies; Elisa Bongetti; Irene Ruderman; Grahame J. Elder; Carmel M. Hawley; Rathika Krishnasamy; Matthew A. Roberts; Meg J. Jardine; Janak R. De Zoysa; Stephen P. McDonald (Kidney International Reports)
Introduction: Calciphylaxis is a rare disorder associated with significant morbidity and mortality. Data registries are an invaluable source of information for rare diseases. We reviewed cases of calciphylaxis recorded in the Australia and New Zealand Dialysis and Transplant Registry (ANZDATA) and evaluated associations and outcomes of this condition. Methods: Data was obtained on all cases of calciphylaxis reported between 2019 and 2022 in Australian and New Zealand patients on kidney replacement therapy (KRT). This cohort was compared to all patients in the registry who received KRT from 2019 to 2022 without an episode of calciphylaxis. Cox proportional hazards regression including a time-varying covariate for calciphylaxis episode was conducted for mortality with models restricted to patients on dialysis only. Results: From 2019 to 2022, 333 patients had calciphylaxis episodes reported. Overall incidence rate for patients on dialysis was 4.5 (4.1–5.1) episodes per 1000 patient-years on dialysis. Median age was 63 (interquartile range [IQR]: 55–73) years, 54% were female, 66% had diabetes, 59% were obese (body mass index [BMI] ≥ 30 kg/m2) and 77% were receiving hemodialysis (HD) treatment. Compared to patients without calciphylaxis (n = 46,526), patients with calciphylaxis were more likely to be older, female, and have diabetes, greater BMI, coronary artery, and peripheral vascular disease. The median time to calciphylaxis was 3.2 (IQR: 0.9–6.7) years after KRT commencement. Half of the patients with calciphylaxis died by 12 months from diagnosis. Adjusted hazard ratio (HR) of mortality for patients on dialysis with calciphylaxis <1 year and 1 to 4 years after an episode was 5.8 (4.9–6.9) and 1.5 (1.0–2.1), respectively compared to patients on dialysis without calciphylaxis. Conclusion: Calciphylaxis is a rare but life-threatening condition in people on KRT with the greatest mortality burden within 12 months of diagnosis.